Pengaruh Profitabilitas, Asset Tangibility, Tingkat Pertumbuhan, dan Non-Debt Tax Shield Terhadap Struktur Modal serta Pengaruhnya Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Manufaktur Asia Tenggara) - Dimita Purba; Lamria Sagala; Rintan Saragih (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
This study aims to determine what factors determine the capital structure and firm value of manufacturing companies listed on the stock exchanges of countries that are members of the Association of South East Asian Nations (ASEAN). The operationalization of the variables used in this study include Return on Assets, Tangibility Assets, Growth Rate, Non-Debt Tax Shield, and Tobins Q. Meanwhile, from various empirical studies conducted, different results were obtained regarding the value of the company. So that it is tested again on all factors that affect the capital structure and also the value of the company